Maternal Inflammatory Bowel Disease During Pregnancy and Infectious Disease in Offspring Younger Than 5 Years: A Population-Based Cohort Study. (9th March 2023) - Ren, Tai; Yu, Yongfu; Wang, Hui; Li, Fei; Zhang, Jun; Li, Jiong
Abstract : INTRODUCTION: Maternal inflammatory bowel disease (IBD) during pregnancy may be associated with increased susceptibility to infection in offspring. We aimed to assess this association, taking into consideration the mediating role of anti-tumor necrosis factor α (anti-TNFα) agents and adverse birth outcomes. METHODS: This population-based cohort study included all live-born singletons born in Denmark during 1995–2016 (n = 1, 343, 960). The exposure was maternal IBD. Main outcome of interest was offspring infection younger than 5 years, defined by either infection-related hospitalization or systemic antibiotic prescription, whose corresponding risk estimates were hazard ratios (HRs) and incidence rate ratios (IRRs), respectively. We applied an inverse probability-weighted marginal structural model for mediation analysis. RESULTS: Offspring born to mothers with Crohn's disease (CD) had an 18% increased risk of infection-related hospitalization (HR 1.18, 95% confidence interval 1.10–1.26) and a 16% increased frequency of prescribed antibiotics (IRR 1.16, 95% confidence interval 1.11–1.21). Anti-TNFα agents could explain 10% and 3% of the 2 estimated total associations, respectively, while a composite of preterm birth, low birth weight, and small for gestational age could explain 4% and 0%, respectively. The association between prenatal anti-TNFα and frequency of antibiotics attenuated after additional adjustment for maternal CD (IRR from 1.23 [0.98–1.55] to 1.10 [0.87–1.40]). Maternal ulcerative colitis, however, was not associated with offspring infection. DISCUSSION: Maternal CD, but not ulcerative colitis, was associated with an increased risk of infection in offspring younger than 5 years, of which adverse birth outcomes and anti-TNFα had a minor role. The association between anti-TNFα agents and pediatric infection could be partially explained by maternal CD.